Feasibility of Quantum Computers in Cryogenic Systems (International Journal of Engineering and Computer Science, 2020)
Quantum computers consist of a quantum processor – sets of quantum bits or qubits operating at an extremely low temperature – and a classical electronic controller to read out and control the processor. The machines utilize the unusual properties of matter at extremely small scales – the fact that a qubit, can represent “1” and “0” at the same time, a phenomenon known as superposition. (In traditional digital computing, transistors in silicon chips can exist in one of two states represented in binary by a 1 or 0 not both).Under the right conditions, computations carried out with qubits are equivalent to numerous classical computations performed in parallel, thus greatly enhancing computing power compared to today’s powerful supercomputers and the ability to solve complex problems without the sort of experiments necessary to generate quantum phenomena.this technology is unstable and needs to be stored in a cool environment for faster and more secure operation.In this paper, we discuss the possibility of integrating quantum computers with electronics at deep cryogenic temperatures.